Spatial and seasonal variations of chlorophyll a in Zhanjiang Bay, China, and controlling factors - Wang, Shuangling; Zhou, Fengxia; Chen, Fajin; Zhu, Qingmei; Meng, Yafei (Frontiers in Marine Science, 2024)
Based on on-site survey data from 26 stations in the surface seawater of Zhanjiang Bay in April (spring), July (summer), September (autumn), and December (winter) of 2017, the spatial distribution characteristics of chlorophyll a (Chl a) and nutrients in the surface seawater of Zhanjiang Bay in different seasons were analyzed, and the regulatory mechanism of chlorophyll a spatiotemporal changes was discussed.The results showed that the Chl a concentrations in the surface water of Zhanjiang Bay are 0.